Changes in renal and metabolic indices after switching from tenofovir disoproxil fumarate– to tenofovir alafenamide–containing ART among individuals with HIV in Canada: A retrospective study. (August 2021) - Shokoohi, Mostafa; Gupta, Meenakshi; Crouzat, Fred; Smith, Graham; Kovacs, Colin; Brunetta, Jason; Chang, Benny; Knox, David; Acsai, Megan; Merkley, Barry; Giolma, Kevin; Fletcher, David; et al.
We assessed renal and metabolic changes associated with switching from tenofovir disoproxil fumarate (TDF)– to tenofovir alafenamide (TAF)–containing regimens among patients with HIV at the Maple Leaf Medical Clinic, Toronto, Canada. Using an electronic medical records retrospective chart review from July 2005 to December 2019, 651 patients aged ≥16 years taking TDF-containing regimens for ≥6 months who switched to TAF-containing regimens for ≥6 months were included. Change in estimated glomerular filtration rate (eGFR) was examined at 12-month follow-up. Secondary outcomes included change in urine albumin-to-creatinine ratio, serum phosphate, alkaline phosphatase (ALP), cholesterol markers, HbA1C, and weight. After 12 months, eGFR increased in 63% of the baseline eGFR <60 mL/min/1.73 m 2 group (mean change [SD] = +5.1 [10.8], p = 0.002), 52% for the baseline eGFR = 60–90 mL/min/1.73 m 2 group (+0.5 [10.4], p = 0.490), and 26% for baseline eGFR >90 mL/min/1.73 m 2 group (−7.2 [11.2], p <0.001). The multivariable generalized estimating equations model showed a significant reduction in eGFR after 12 months. Advanced age, HCV coinfection, and being switched to or on integrase inhibitors were significantly associated with reduced eGFR. Among secondary outcomes, ALP significantly decreased, while high-density lipoprotein, low-density lipoprotein, and weight significantly increased. Our findings suggest that TDF-to-TAF switching was beneficial for those with preexisting renal impairment (eGFR <60 mL/min/1.73 m 2 ).